'Just 5 more minutes!' Power dynamics in outdoor play. Issue 1 (2nd January 2019) - Canning, Natalie
ABSTRACT: This paper considers power dynamics between children, parents and early childhood educators in an outdoor environment. Drawing on sociocultural theory the paper considers how power is constructed and viewed in relation to children's play. The research focuses on three case study examples of outdoor social group play where power dynamics influence children's choices and decisions, how they respond and how they negotiate to follow their play interests. The paper considers some of the dilemmas and intricacies of power dynamics between children, adults and the environment exploring the way in which children navigate those situations so that they can achieve 'just 5 more minutes' playing.